Identification of Microplastics in Sediments in Limboto Lake - Jahja, Mohamad; Demulawa, Meilan; Mohamad, Humaira (Peneliti.net, 2024)
Lake Limboto is a lake that has several natural resources. Lake Limboto is currently experiencing pollution caused by the large amount of plastic waste. This study aims to determine the shape and color of microplastics in the sediment. Microplastics are a type of waste less than 5 mm in size. Based on the results of the study and discussion of the physical characteristics of microplastics contained in the sediment in Lake Limboto, it can be concluded that the identification of microplastics in the sediment consists of microplastics in the form of fibers with colors at location 1 purple, black and red, location 2 purple, location 3 black, and location 4 black.